Cutaneous Reactions in Children Treated with the Mitogen‐Activated Protein Kinase Extracellular Signal‐Regulated Kinase Inhibitor Trametinib for Neural Tumors. Issue 1 (16th December 2016) - Boull, Christina; Hook, Kristen; Moertel, Christopher; Maguiness, Sheilagh
Abstract: Background: The mitogen‐activated protein kinase (MAPK) pathway is a target for the treatment of a growing number of malignancies. The cutaneous reactions to medications that inhibit this pathway have not been described in children. Methods: A retrospective chart review was completed for eight children with neural tumors treated with the MAPK extracellular signal‐regulated kinase inhibitor trametinib. All children were evaluated by a pediatric dermatologist with documentation of cutaneous findings. Results: All patients had at least two separate skin reactions while on treatment with trametinib. Common skin findings included xerotic dermatitis, bacterial folliculitis, acneiform eruptions, paronychia, and hair thinning. No child needed to discontinue use of trametinib due to cutaneous toxicities. Conclusions: Cutaneous reactions are common in children receiving trametinib. Identification of these reactions is the initial step in establishing treatment guidelines that will minimize skin eruptions and subsequent interruption of trametinib treatment.